Compound C Reducing Interferon Expression by Inhibiting cGAMP Accumulation - Lai, Junzhong; Luo, Xuan; Tian, Shuoran; Zhang, Xing; Huang, Shanlu; Wang, Hanze; Li, Qiumei; Cai, Shaoli; Chen, Qi (Frontiers in Pharmacology, 2020)
Cyclic GMP-AMP (cGAMP) synthase (cGAS) is a major DNA sensor responsible for cytosolic DNA–mediated innate immune response. Inhibition of cGAS may be an effective strategy for treating autoimmune diseases such as Aicardi-Goutieres syndrome and systemic lupus erythematosus. Compound C (also known as Dorsomorphin) has been annotated as a potent and reversible inhibitor for AMPKs as well as ALK protein kinases. Here, we report a new function of Compound C which can suppress dsDNA-dependent type I interferon induction. These effects were not dependent on the activities of AMPK proteins. In vitro assays and liquid chromatograph-mass spectrometry data show that Compound C has the capability of reducing cGAMP synthesis, suggesting that Compound C may function as a cGAS inhibitor. Furthermore, Compound C is able to rescue the autoimmune phenotypes in a mouse model carrying the Trex1 gene deficiency. These data demonstrate a new and inverse correlation between Compound C and type I interferon production in response to dsDNA signaling.